Cervical Cancer Visual Screening Experience in the Republic of Tajikistan - Muhsinzoda, Nilufar; Bingjie Yuan, Alex; Tursunov, Rustam (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVES: To study the results of the first pilot study of organized visual cervical cancer (CC) screening for the detection of precancerous pathology of the cervix in two pilot districts of the Republic of Tajikistan. STUDY DESIGN: In this cross-sectional study, the target group included healthy women of reproductive age (30-49 years) from Kushoniyon and B. Gafurov Districts who underwent visual screening. The total study population was 72,574 out of which 68,391 (94.3%) visited primary healthcare facilities for visual inspection with Lugol’s Iodine (VILI). A total of 2958 women with suspicious tests for cervical intraepithelial neoplasia (CIN) were identified (4.3%) and sent to the reproductive health care centers for further diagnostics. Post-screening diagnostic tests were performed to specify cervical lesions, which included colposcopy with acetic acid (VIA) visual inspection, cytology, and biopsy with histological examination. HPV testing wasn’t included in the diagnostic protocol due to its high cost. RESULTS: A total of 164 histologically confirmed cases of CIN were identified (0.25% of number of women screened). The detection rate of precancerous pathology was 26.9 per 100,000 female population, which is 8.2 times higher than the detection rate of CC. All patients regardless of CIN degree underwent loop electrosurgical excision (LEEP)/conization. In the follow-up period (6-48 months), complete recovery after 136 LEEP, 21 conizations, and 7 hysterectomies were observed in 97% (5 recurrences of non-invasive disease). CONCLUSION: The visual screening showed high efficiency in detecting CIN. The positive experience suggests the implementation of this program nationwide.